THE CONCEPT OF GENDERLECT AS A SET OF CHARACTERISTICS OF MALE AND FEMALE SPEECH: THE CONCEPT OF GENDERLECT AS A SET OF CHARACTERISTICS OF MALE AND FEMALE SPEECH - Davlatboeva, Adiba (Журнал иностранных языков и лингвистики, 2025)
The concepts of "gender," "men’s and women’s speech," which are currently encountered in domestic linguistics, originate from the concept of "gender." The concept of "gender" has penetrated all humanities - philosophy, sociology, psychology, history, linguistics, literary studies, etc. - it is constantly changing and enriching. This is explained, firstly, by the fact that the concept itself arose relatively recently; secondly, by its complexity. Therefore, let’s examine the scope of the concept in more detail.